2019
DOI: 10.1002/jcb.29311
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria could be a potential key mediator linking the intestinal microbiota to depression

Abstract: The intestinal microbiota has been reported to affect depression, a common mental condition with severe health‐related consequences. However, what mediates the effect of the intestinal microbiota on depression has not been well elucidated. We summarize the roles of the mitochondria in eliciting beneficial effects on the gut microbiota to ameliorate symptoms of depression. It is well known that mitochondria play a key role in depression. An important pathogenic factor, namely inflammatory response, may adversel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 91 publications
(292 reference statements)
0
22
0
Order By: Relevance
“…Gut microbiota has often been linked with metabolic diseases such as NAFLD, diabetes and obesity [ 3 , 4 ]. Many studies have shown that dysregulation of the intestinal microbiota (gut dysbiosis) can lead to NAFLD [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbiota has often been linked with metabolic diseases such as NAFLD, diabetes and obesity [ 3 , 4 ]. Many studies have shown that dysregulation of the intestinal microbiota (gut dysbiosis) can lead to NAFLD [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The probiotic Faecalibacterium prausnitzii is known to confer an antidepressive effect through its ability to produce an abundance of butyrate and reduce IL-6 level [38]. Butyrate, a short-chain fatty acid (SCFA) produced by gut microbiota, confers a protective role on the gut permeability and exerts anti-inflammatory effects on various organs including the brain [114]. Butyrate has been demonstrated to ameliorate depressive symptoms and likened to an anti-depressant in mice models [58].…”
Section: Inflammationmentioning
confidence: 99%
“…The development of autism spectrum disorder possibly implicates mediating effects of mitochondrial function induced by colonic butyrate [14]. Neuronal mitochondrial dysfunction (affecting neuronal function and neuron cell numbers) may mediate the effects of gut dysbiosis on depression [51]. Possible pathways include SCFAs, brain inflammatory processes following gut permeability and increased blood lipopolysaccharide (LPS) levels [51].…”
Section: Mitochondrial Functionmentioning
confidence: 99%